The Australia Telescope 20-GHz (AT20G) Survey: the Bright Source Sample - Massardi, M.; Ekers, Ronald; Murphy, T.; Ricci, R.; Sadler, E.; Burke, S.; De Zotti, G.; Edwards, P.; Hancock, Paul; Jackson, Carole; Kesteven, M.; Mahony, E.; et al. (Oxford University Press, 2008)
The Australia Telescope 20-GHz (AT20G) Survey is a blind survey of the whole southern sky at 20 GHz (with follow-up observations at 4.8 and 8.6 GHz) carried out with the Australia Telescope Compact Array from 2004 to 2007. The Bright Source Sample (BSS) is a complete flux-limited subsample of the AT20G Survey catalogue comprising 320 extragalactic (|b| > 1. ? 5) radio sources south of d = -15? withS20 GHz > 0.50 Jy. Of these, 218 have near simultaneous observations at 8 and 5 GHz. In this paper we present an analysis of radio spectral properties in total intensity and polarization, size, optical identifications and redshift distribution of the BSS sources. The analysis of the spectral behaviour shows spectral curvature in most sources with spectral steepening that increases at higher frequencies (the median spectral index a, assuming S ? ?a, decreases from a8.6 4.8 = 0.11 between 4.8 and 8.6 GHz to a20 8.6 = -0.16 between 8.6 and 20 GHz), even if the sample is dominated by flat spectra sources (85 per cent of the sample has a20 8.6 > -0.5). The almost simultaneous spectra in total intensity and polarization allowed us a comparison of the polarized and total intensity spectra: polarized fraction slightly increases with frequency, but the shapes of the spectra have little correlation. Optical identifications provided an estimation of redshift for 186 sources with a median value of 1.20 and 0.13, respectively, for QSO and galaxies.